Efektivitas Pembelajaran PAK Kurikulum Merdeka dengan Metode Snowball Throwing Berbantuan Modul terhadap Prestasi Belajar di SMA Sint Louis Semarang - Damiana Yasinta Ambu; Andarweni Astuti; Anselmus Joko Prayitno (Publisher STPKat, 2025)
The existence of problems Incompletion and weak achievement of students' learning at SMA Sint Louis Semarang is caused one only by the lack of attention of some students towards PAK learning material the research aims to: 1) To find out the use of the snowball throwing method has achieved completeness results in the Sint Lous High School students in the independent learning curriculum 2) To find out the influence of the aspect of independence on the use of the snowball throwing method on the learning achievement of the participants Sint Louis High School students in the independent learning curriculum 3) To find out the effectiveness of achievement learning using the snowball throwing method for class X Sint Louis High School Semarang in the Independent learning Curriculum. To get answers to these problems researchers used research methods quantitative experiments. By using independence instruments. The population in this research is all students in class X SMA Sint Louis Semarang. With the sample used being all students of class posttest The results obtained were the difference between the average pretest score of 40 and after the posttest the average was 95. Therefore, it is concluded that PAK learning in the independent curriculum using the snowball method throwing rocky modules is effective on the learning achievement of students class X SMA Sint Louis Semarang. Suggestions it is necessary to add other methods so that the learning process in class is not monotonous and is able to encourage student activity